Democracy in New Zealand - Miller, Raymond (Auckland University Press, 2015)
An up-to-date and concise introduction to New Zealand politics and how it works. New Zealand is one of the world's oldest democracies for men and women, Maori and Pakeha, with one of the highest political participation rates. But from MMP to leadership primaries, spin doctors to dirty politics' the country's political system is undergoing rapid change. Democracy in New Zealand provides Examining the constitution and the political system, cabinet and parliament, political parties, leadership and elections, Raymond Miller draws on data and analysis (including from the 2014 election) to tackle critical questions: Who runs New Zealand? Does political apathy threaten democracy? Will new parties have an ongoing impact? Do we now have a presidential democracy? Democracy in New Zealand is an ideal university text